Effect of epigenetic inhibitors on adipogenesis in human periodontal ligament stem cells = Efecto de inhibidores epigéneticos en la adipogénesis en células troncales del ligamento periodontal humano - Montero Del Toro, Julio A.
Histone H3 lysine 9 acetylation is a crucial epigenetic mark in mesenchymal stem cell differentiation processes like adipogenesis. This study aimed to evaluate the effect of epigenetic inhibitors on adipogenesis in human periodontal ligament stem cells, using histone deacetylase inhibitors such as valproic acid and trichostatin A. The cells were treated independently with 8 mM valproic acid and 100 nM trichostatin A for 72 hours to inhibit class I histone deacetylases. Subsequently, the cells underwent adipogenic induction for 28 days. Morphology and intracellular lipid deposition were analyzed using Oil-Red oil staining. Protein extracts were prepared on days 0 and 28 to analyze histone H3 lysine 9 acetylation levels via Western blot. Our results demonstrated that cells treated with either VPA or TSA showed, on average, a 1.275-fold increase in lipid deposition during the adipogenic process, with no significant differences between the treatments compared to the control group. Further, by day 28, histone H3 lysine 9 acetylation levels were 1.43 times higher in cells treated with valproic acid and 2.52 times higher in those treated with trichostatin A.These findings suggest that the inhibitors could have differential effects on chromatin remodeling in different regions by increasing acetylation, contributing indistinctly to lipid deposition due to the greater expression of genes associated with the adipogenic phenotype.